Design of an embedded control scheme for control of remote appliances - Jipeng, Tian; Neelagar, Mahesh B; Prasad N., Achyutha; V.S, Rekha (Journal of Advanced Research in Instrumentation and Control Engineering, 2021)
In today’s world remote control over the electronic appliances is of the utmost importance. The conventional techniques are either wired or work on a line of sight communication and hence put a limit on the range over they can be operated. In today’s era communication system is bringing the world closer and telecommunication is one of the inevitable parts and serves the best medium to control the appliances. The objective of the work presented here is to control the appliances / devices from any corner of the world, which can be effectively, achieved through telephonic control since the telephonic network covers the entire globe. This work employs the same technique for controlling various devices through the telephone line. [1] The basic heart of this research work is the DTMF tone. All the data required to control the appliances is based on the detection of the DTMF tone. The output of the DTMF decoder comes out to be in a digital form and hence is directly compatible with the microcontroller and hence highlights a new path to the user authentication process and automatic termination of call on system or line malfunction. All the above-mentioned requirements can be fulfilled through an electronic circuit that consists of ring detector, hook switch, DTMF tone decoder, noise canceller, latch and a microcontroller. How to cite this article: Jipeng T, Neelagar MB, Prasad AN. Design of an Embedded Control Scheme for Control of Remote Appliances. J Adv Res Instru Control Engg 2020; 7(3&4): 5-8